2020
DOI: 10.2147/cmar.s272498
|View full text |Cite
|
Sign up to set email alerts
|

<p>Inhibition of microRNA-15b-5p Attenuates the Progression of Oral Squamous Cell Carcinoma via Modulating the <em>PTPN4</em>/STAT3 Axis</p>

Abstract: Background Emerging evidence has demonstrated the important functions of microRNAs (miRNAs) in human malignancies. This study focuses on the function of miR-15b-5p on the oral squamous cell carcinoma (OSCC) progression and the molecules involved. Methods Tumor and the paracancerous tissues were obtained from OSCC patients. Differentially expressed miRNAs between the tumor and normal tissues were screened out. miR-15b-5p expression in tumors and acquired cells was determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 34 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…This study should, in the future, be expanded to other validated targets of miR-15b-5p and SFN. For instance, miR-15b-5p affects LATS2 [78], PTPN4/STAT3 [79], HPSE2 [80], axin2 [81] and RECK [32] in human cancers. On the other hand, SFN down-regulates CDK4/CDK6, inhibits tubulin polymerization [82], inhibits STAT3/HIF-1alpha/VEGF signaling [83], induces ERK1/2 and caspase-3 [51] and targets NRF2 [84] and other transcriptions factors [85].…”
Section: Discussionmentioning
confidence: 99%
“…This study should, in the future, be expanded to other validated targets of miR-15b-5p and SFN. For instance, miR-15b-5p affects LATS2 [78], PTPN4/STAT3 [79], HPSE2 [80], axin2 [81] and RECK [32] in human cancers. On the other hand, SFN down-regulates CDK4/CDK6, inhibits tubulin polymerization [82], inhibits STAT3/HIF-1alpha/VEGF signaling [83], induces ERK1/2 and caspase-3 [51] and targets NRF2 [84] and other transcriptions factors [85].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that PTPN4 was a signaling molecule of several important pathways, including signal transducer and activator of transcription 3 (STAT3), toll like receptor 4 (TLR4), mitogen-activated protein kinase 1 (MAPK1), etc. [31][32][33][34]. TFCP2L1 is a transcription regulating factor and is reported to play key roles in inflammation by regulating KLF transcription factor 4 (KLF4)/ ras homolog family member F (RHOF)/NF-κB pathway [35].…”
Section: Discussionmentioning
confidence: 99%
“…CREB5 expression was significantly higher in active CD than in inactive CD ( 59 ), which agrees with our in silico analysis in patients with recurrent CD. All these referred pathways have been summarized up in a supplementary Table 3 (see Supplementary Digital Content 3, http://links.lww.com/CTG/A706 ) ( 35 , 36 , 39 42 , 44 46 , 48 , 60 65 ).…”
Section: Discussionmentioning
confidence: 99%